FORMULASI PRODUK BOLU TEPUNG UBI UNGU TEPUNG KACANG MERAH SEBAGAI ALTERNATIF MAKANAN SELINGAN ANAK AUTIS - Zahirah, Siti Zahra; Suparman, Suparman; Saleky, Yohannes Willihelm; Mulyo, Gurid PE (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2022)
Sweet Potatoes and Red Beans can be processed into Steamed Sponge. This study discusses the manufacture of steamed cake products made from purple sweet potato flour and red bean flour which contains energy, protein, fat, and carbohydrates and is free from gluten-casein and prebiotic sources needed to fulfill nutrition in children with autism. This study aims to determine the best balance of the product fromthe 3 balances of purplesweet potatoflour and red bean flour, the effect of differences in the balance of steamed cake on the color, aroma, taste, and texture of the product, and to determine the levels of macronutrients and prebiotic levels. Experimental study research design with Completely Randomized Design (CRD). The research method used hedonic test to determine organoleptic properties, proximate analysis for macronutrients, and raffinose calculations for prebiotics. The results of the Kruskal Wallis test showed that there was a significant difference in the hedonic test on color and texture. F1 excels in the aspects of color, aroma, and taste. It is hoped that further research can be carried out on the effect of giving Purple Potato Flour and Red Bean Flour Steamed Sponge to children with autism.